USE OF SOLAR ENERGY FOR THE PROVISION OF COST-EFFECTIVE AND ENVIRONMENTALLY FRIENDLY POWER SUPPLY IN HEALTH FACILITIES IN THE DEVELOPING WORLD- LESSONS FROM A COMMUNITY COTTAGE HOSPITAL IN SOUTHERN NIGERIA - Emmanuel E. Ekanem, Akinwunmi O. Fajola, Rebecca Ogbimi3 & Julius I. OgievaB4 (International Journal of Research Science and Management, 2017)
Erratic public electric power supply has been a perennial problem in Nigeria since its creation by the British in 1914. It affects all sectors of the economy including the health sector with important dependence on fossil fuel driven generators as alternative or back up, with adverse consequences including emission of toxic gases, noise and high costs. Clean and renewable power sources have been recommended as viable and better alternatives. In a Community Cottage Hospital in southern Nigeria, jointly run by Shell Petroleum Development Company and the Rivers State of Nigeria, solar power introduced in 2010 as alternative electricity supply system. From an average of sixteen hours of power supply a day, a twenty-four electricity power supply a day was achieved since then with a continuing reduction in dependence in fossil fuel. Cost of power was also reduced from 300- 1500 to 180-500 a month. Patronage of the facility by the public has also increased since the installations. Solar energy systems are easy to install, operate and maintain by small and medium size institutions. With abundant sunlight all year round, this model is recommended for supply of electric power and solar pumps for hospitals, households and similar institutions in Nigeria and the environments.